The role of foresight in bridging the gap between trends and customer experiences - Daniel Fasnacht; Janine Schlosser (European Journal of Futures Research)
Abstract Anticipating trends and adapting strategies to navigate an increasingly dynamic and complex business environment are essential for organisational success. This paper explores key challenges in effective decision-making, with a focus on integrating foresight practices into strategy and leadership at SWISS International Airlines. It identifies significant gaps between the recognition of emerging trends and their translation into tangible customer value. To address the need for a systematic approach to embedding foresight into the travel experience, we advocate for stronger intra-organisational collaboration. Such collaboration enhances communication and is essential for managing the intricacies of large, multi-layered organisations while ensuring strategic alignment across functional and hierarchical boundaries. By positioning foresight as a foundational element of strategic planning, organisations can unlock new pathways for customer value, foster innovation, and strengthen resilience. This approach not only bridges the gap between trend identification and customer experience but also offers transferable insights for other industries aiming to leverage foresight as a source of strategic advantage.